Reduction method of hexavalent chromium
By loading polyindole on nano-scale magnetic Fe3O4 particles, a heterojunction photocatalyst is constructed, and photogenerated electron separation is used to solve the problem of low efficiency of the existing hexavalent chromium reduction method, and efficient hexavalent chromium reduction and chromium resources are achieved Recycle.
Patent Information
- Application Number
- CN202411637952.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing hexavalent chromium reduction methods have problems such as low reduction efficiency and difficulty in recycling.
By supporting nanoscale magnetic Fe3O4 particles with polyindole, a heterojunction photocatalyst (Fe3O4@Pind) is constructed, and photogenerated electrons are used to separate them at the heterointerface to promote the reduction of hexavalent chromium.
Under ultraviolet light, Fe3O4@Pind can efficiently reduce hexavalent chromium, realizing the removal of hexavalent chromium and the resource recycling of chromium, significantly improving the reduction efficiency.
Smart Images

Figure CN119461623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental governance, and in particular to a method for reducing hexavalent chromium. Background Art
[0002] Chromium exists mainly in the form of hexavalent chromium oxygen-containing anions and trivalent chromium cations. Hexavalent chromium is highly toxic to organisms, but trivalent chromium is essential as a trace element in the human body. At present, hexavalent chromium treatment technologies mainly include adsorption, membrane separation, ion exchange, electrochemical and chemical precipitation. Among them, chemical precipitation belongs to the reduction method, which uses a reducing agent to reduce heavy metal ions to metal elements or metal ions with lower valence, and has great potential in the recovery of heavy metals. Polybenzidine (Pind) can be photoionized by ultraviolet irradiation to produce photogenerated electrons with strong reducing properties, which can reduce the coexisting hexavalent chromium to trivalent chromium with low toxicity, and its own structure is stable and can be reused in the reaction. Magnetic substances, such as ferroferric oxide, have good excellent magnetic properties, low toxicity and high specific surface area, and can be used as a good recyclable carrier in the environmental field. In theory, the energy band position of Fe3O4 and the energy band position of polybenzidine (Pind) are misaligned, which can form a Z-type heterojunction, prolong the charge separation time, and enhance the interfacial charge transfer. Therefore, the present invention composites magnetic Fe3O4 particles with Pind to construct a heterojunction photocatalyst (Fe3O4@Pind), which can efficiently adsorb and reduce hexavalent chromium, thereby achieving the removal of hexavalent chromium and the resource recovery of chromium, which is of great significance for addressing chromium pollution. Summary of the invention
[0003] The invention provides a hexavalent chromium reduction method, which is used to solve the problems of low reduction efficiency and difficulty in recovery in the existing hexavalent chromium reduction method.
[0004] According to a first aspect of the present invention, the present invention provides a method for reducing hexavalent chromium, comprising the following steps: Preparation of nano-sized magnetic Fe3O4 particles and loading of polybenzazole; The synthesized nano-scale magnetic Fe3O4 particles loaded with polybenzazole are mixed with hexavalent chromium to form a mixed solution; the formed mixed solution is irradiated with light so that the nano-scale magnetic Fe3O4 particles are loaded with polybenzazole to construct a heterojunction photocatalyst to promote the reduction of hexavalent chromium.
[0005] The principle of the present invention is: Photogenerated electrons have strong reducing properties, high reduction rates for hexavalent chromium, and good application prospects. The reduction method of the present invention transfers the photogenerated electrons generated by Fe3O4 to polybenzazole, and the holes generated by polybenzazole can be transferred to Fe3O4, so that the constructed heterogeneous interface promotes the separation of electron-hole pairs. In this way, the purpose of continuously generating photogenerated electrons and effectively reducing hexavalent chromium under ultraviolet light is achieved, which is of great significance for addressing the problem of hexavalent chromium environmental pollution.
[0006] Furthermore, the preparation of Fe3O4@Pind specifically includes the following steps: Weigh ferric chloride, sodium acetate, and trisodium citrate and dissolve them in ethylene glycol and diethylene glycol solutions to form a mixed solution; The mixed solution is shaken, subjected to a high temperature solvent thermal reaction, and then cooled to room temperature to form a nano-scale magnetic Fe3O4 solution; Weigh indole and dissolve it in the nano-magnetic Fe3O4 solution to form an indole mixed solution; weigh ammonium persulfate and dissolve it in pure water to form an ammonium persulfate solution; The ammonium persulfate solution is added dropwise into the indole mixed solution, and then the solution is shaken, and then filtered to obtain nanoscale magnetic Fe3O4 particles loaded with polybenzazole; the nanoscale magnetic Fe3O4 particles loaded with polybenzazole are repeatedly washed with pure water to remove impurities, and then vacuum dried and sieved to obtain nanoscale magnetic Fe3O4 particles loaded with polybenzazole.
[0007] In the above scheme, after synthesizing nanoscale magnetic Fe3O4 particles, the indole monomer is oxidatively polymerized under the action of ammonium persulfate oxidant to generate polyindole by chemical oxidation method, thereby obtaining nanoscale magnetic Fe3O4 particles loaded with polyindole, and successfully constructing Fe3O4@Pind, in order to retain the structure and magnetic properties of ferrosoferric oxide while having the reducing property of polyindole, thereby continuously and stably generating hydrated electrons.
[0008] Furthermore, the ratio of ethylene glycol to diethylene glycol in the mixed solution is (2-10): (1-5), preferably 2:1; the concentration of ferric chloride in the mixed solution is 5-15, preferably 9.9-10.1 g / L; the concentration of sodium acetate in the mixed solution is 30-75, preferably 49.9-50.1 g / L; the concentration of trisodium citrate in the mixed solution is 10-20, preferably 14.9-15.1 g / L.
[0009] In the above scheme, by limiting the concentration of each substance in the mixed solution to a reasonable range, it is beneficial to improve the efficiency of the polymerization reaction.
[0010] Furthermore, the shaking speed is 400-600 rpm, and the time is 25-35 minutes; preferably, the shaking speed is 500 rpm, and the time is 30 minutes.
[0011] In the above scheme, by limiting the shaking speed and time within a reasonable range, it is beneficial for the polymerization reaction to proceed fully.
[0012] Further, the temperature of the high-temperature solvent thermal treatment is 190-210° C., and the time is 9-11 hours; preferably, the temperature of the high-temperature solvent thermal treatment is 200° C., and the time is 10 hours.
[0013] In the above scheme, the temperature and time of the high-temperature solvent heating are limited within a reasonable range, which is conducive to the full progress of the polymerization reaction.
[0014] Furthermore, the concentration of indole in the indole mixed solution is 1.6-1.7 g / L.
[0015] In the above scheme, by limiting the concentration of indole in the indole mixed solution to a reasonable range, the efficiency of the polymerization reaction is improved.
[0016] Furthermore, the concentration of the sodium persulfate solution is 1.9-2.1 g / L.
[0017] In the above scheme, by limiting the concentration of the sodium persulfate solution within a reasonable range, the efficiency of the polymerization reaction is improved.
[0018] Furthermore, the pure water is pure water at room temperature; and / or the vacuum drying is vacuum drying at 60° C. for 12 hours.
[0019] In the above scheme, by selecting a suitable type of washing solvent, impurities on the nano-scale magnetic Fe3O4 particles loaded with polybenzazole can be fully washed away to improve the purity of the product. By limiting the conditions of vacuum drying, the purpose of high-quality drying can be achieved.
[0020] Further, the synthesized Fe3O4@Pind is mixed with hexavalent chromium to form a mixed solution; the formed mixed solution is irradiated with light so that the constructed Fe3O4@Pind nanoscale magnetic Fe3O4 particles are loaded with polybenzazole to construct a heterojunction to promote the reduction of hexavalent chromium, which specifically includes the following steps: Prepare hexavalent chromium aqueous solution; The synthesized Fe3O4@Pind is dispersed in the prepared hexavalent chromium aqueous solution, and the pH value is adjusted to 3.0-4.0, and then stirred evenly to form a mixed solution; a mercury lamp is used as a light source for illumination, and the light is turned on to carry out a reduction reaction.
[0021] In the above scheme, by functionalizing polybenzazole nanoparticles on the surface of nanoscale magnetic Fe3O4 particles to construct a heterojunction, the electron-hole separation efficiency can be effectively improved and the electron lifetime can be extended, thereby promoting the reduction of hexavalent chromium.
[0022] Furthermore, the reduction reaction system is an open system and is not isolated from air.
[0023] In the above scheme, the reduction reaction system is an open system without air isolation, which makes the degradation conditions simple and not harsh.
[0024] Furthermore, the reduction reaction temperature is controlled at 25±1° C., the reaction time is 0.5-3 h, and the light source is a 300W mercury lamp, the wavelength of the emitted light is mainly concentrated at 365 nm.
[0025] In the above scheme, the reduction efficiency can be improved by reasonably selecting the temperature, time and light source of the reduction reaction.
[0026] Furthermore, in the mixed solution, the concentration of Fe3O4@Pind in the mixed solution is 0.05-0.5 g / L, and the water used in the reaction is ultrapure water.
[0027] In the above scheme, by limiting the contents of Fe3O4@Pind and hexavalent chromium in the mixture, Fe3O4@Pind can more effectively reduce hexavalent chromium, thereby improving the reduction efficiency.
[0028] The invention discloses a method for reducing hexavalent chromium. Nano-sized magnetic Fe3O4 particles are loaded with polybenzazole to construct a heterogeneous interface to generate photogenerated electrons. The photogenerated electrons generated by Fe3O4 are transferred to polybenzazole, and the holes generated by polybenzazole can be transferred to Fe3O4. Thus, the constructed heterogeneous interface promotes the separation of electron-hole pairs. This achieves the purpose of continuously generating photogenerated electrons and effectively reducing hexavalent chromium under ultraviolet light, which is of great significance for addressing the problem of hexavalent chromium environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 This is the infrared spectrum of Fe3O4@Pind obtained in Example 1 of the present invention; Figure 2 The XRD spectrum of Fe3O4@Pind obtained in Example 1 of the present invention; Figure 3 This is a comparison chart of the reduction rates of hexavalent chromium by different materials in Example 1 of the present invention; Figure 4 This is a graph showing the reduction rate of hexavalent chromium at different concentrations of Fe3O4@Pind and hexavalent chromium in Example 2 of the present invention; Figure 5 This is a graph showing the reduction rate of hexavalent chromium of Fe3O4@Pind at different pH values in Example 3 of the present invention, reaction conditions: C0(Cr): 50 mg / L; Figure 6 This is a comparison chart of the reduction rate of hexavalent chromium of Fe3O4@Pind under different anion concentrations in Example 4 of the present invention, reaction conditions: C0(Cr): 50 mg / L. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0033] This embodiment provides a method for reducing hexavalent chromium, which specifically includes the following steps: (1) Preparation and characterization of Fe3O4@Pind: Take 120mL ethylene glycol and 60mL diethylene glycol into a beaker and mix them well, then quickly add 1.8g ferric chloride, 9g sodium acetate and 2.7g trisodium citrate, stir and dissolve. The mixed solution was shaken at 500 rpm for 30 minutes, and then subjected to high temperature solvent thermal reaction at 200°C for 10 hours, and then cooled to room temperature to form a nanoscale magnetic Fe3O4 solution. Weigh 0.3g indole and dissolve it in the nanoscale magnetic Fe3O4 solution to form an indole mixed solution; then, 33mL aqueous solution dissolved with 0.067g ammonium persulfate was added dropwise. The mixed solution was shaken at 500 rpm for 30 minutes. The nanoscale magnetic Fe3O4 particles loaded with polybenzazole were repeatedly washed with pure water to remove impurities, and then vacuum dried at 60°C for 12h. Finally, polybenzazole was ground using an agate mortar and passed through a 100-mesh sieve to obtain nanoscale magnetic Fe3O4 particles loaded with polybenzazole, and Fe3O4@Pind was successfully prepared.
[0034] The prepared Fe3O4@Pind was characterized by infrared spectroscopy ( Figure 1 ), compared with the infrared spectrum of polybenzazole reported in the literature, at 1107cm-1 The stretching vibration of the benzene ring structure of polyindole was observed, proving that polyindole was successfully loaded.
[0035] The prepared Fe3O4@Pind was characterized by XRD ( Figure 2 ), compared with the prepared polybenzazole and magnetic ferroferric oxide XRD patterns, the Fe3O4@Pind curve showed 5 peaks, corresponding to different crystal planes of Fe3O4 (220), (311), (400), (511), and (440). Fe3O4@Pind would not change the position of its peaks, indicating that the Fe3O4 crystal structure was well preserved.
[0036] (2) Photochemical reduction reaction: Before the reduction reaction, first prepare a 50 mg / L hexavalent chromium aqueous solution, then disperse Fe3O4@Pind in the hexavalent chromium aqueous solution, and use 0.1 M NaOH and HCl to adjust the pH of the solution to 3.0. Use magnetic stirring to stir the prepared reaction solution for 0.5 hours to form a mixed solution. Transfer the prepared mixed solution to a quartz reaction tube, use magnetic stirring to stir the reaction solution so that it reacts evenly during the reaction. Place a mercury lamp in the middle of the reaction device, close to the reaction solution, react in a dark environment for 30 minutes, and then turn on the light for reduction reaction. The reaction volume is 20 mL, the reaction temperature is controlled at 25±1℃, the reaction time is 3 hours, and the light source is a 300W mercury lamp (the wavelength of the emitted light is mainly concentrated at 365nm). The contents of Fe3O4@Pind and hexavalent chromium in the reaction solution are 0.5 g / L and 50 mg / L, respectively. 1 mL of sample was collected every 30 minutes and the residual content of hexavalent chromium was detected by diphenylcarbazide colorimetry and UV-Visible Spectrophotometer to calculate the reduction rate of hexavalent chromium.
[0037] From the experimental results, we can know that ( Figure 3 ), using only ultraviolet irradiation, after 3 hours of reaction, the reduction rate of hexavalent chromium is about 8%. After adding polybenzazole, the reduction rate of hexavalent chromium is about 84% after 3 hours of reaction; after adding nano-scale magnetic Fe3O4 particles, the reduction rate of hexavalent chromium is about 100% after 3 hours of reaction. After adding Fe3O4@Pind, the reduction of hexavalent chromium is greatly promoted. Hexavalent chromium can be completely reduced after 1 hour of reaction, and the reduction rate of hexavalent chromium is about 100%. The reaction system is an open system and is not isolated from air. The experimental results show that under ultraviolet irradiation, Fe3O4@Pind can enhance the interfacial charge transfer while increasing the redox potential, and generate photogenerated electrons under ultraviolet irradiation to efficiently reduce hexavalent chromium. Example 2
[0038] This example studies the reduction rate of hexavalent chromium under different concentrations of Fe3O4@Pind and hexavalent chromium ( Figure 4 ). Four concentrations of Fe3O4@Pind in the system were set, namely 0.05g / L, 0.1g / L, 0.2g / L, and 0.5g / L, wherein the hexavalent chromium concentration of the same batch remained unchanged. A total of 4 batches were set, and the hexavalent chromium concentrations were set to 10mg / L, 25mg / L, 50mg / L, and 100mg / L, respectively. The other reaction conditions were the same as the photochemical reduction reaction in Example 1. The results show that the reduction efficiency of hexavalent chromium is proportional to the amount of Fe3O4@Pind used. As the concentration of hexavalent chromium increases, the reduction rate of hexavalent chromium by Fe3O4@Pind decreases, but it still has certain reduction performance. Example 3
[0039] This example studies the reduction rate of hexavalent chromium in Fe3O4@Pind at different pH values ( Figure 5 ). Five pH values were set, namely 2, 3, 4, 6, and 8; the concentration of hexavalent chromium remained unchanged and was controlled to be 50 mg / L; the concentration of Fe3O4@Pind in the system remained unchanged and was controlled to be 0.5 g / L. The other reaction conditions were the same as the photochemical reduction reaction in Example 1. The results showed that the adsorption performance of Fe3O4@Pind for Cr(VI) at pH values of 6 and 8 was much lower than that at pH values of 2, 3, and 4. When the pH value was 3, the optimal hexavalent chromium reduction rate was achieved. Example 4
[0040] This example studies the reduction rate of hexavalent chromium in Fe3O4@Pind at different anion concentrations compared to the change without adding each ion ( Figure 6 ). The concentrations of four different anions in the Fe3O4@Pind system were set, namely nitrate ion, phosphate ion, sulfate ion and chloride ion. A total of 4 batches were set, and the concentrations of each anion were set to 5 mg / L, 10 mg / L, 20 mg / L, and 50 mg / L, respectively. The other reaction conditions were the same as the photochemical reduction reaction in Example 1. The results show that, except for nitrate ions, which have almost no effect on the reaction system, the coexisting anions have a negative impact on the photoreduction of hexavalent chromium, and the order is as follows: phosphate ion>sulfate ion>chloride ion.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for reducing hexavalent chromium, characterized in that: The steps include: Prepare nano-sized magnetic Fe3O4 particles and load polybenzazole to construct a heterojunction photocatalyst of magnetic Fe3O4 particles and polybenzazole; The synthesized magnetic Fe3O4 particles and polyindole heterojunction photocatalyst are mixed with hexavalent chromium to form a mixed solution; the formed mixed solution is irradiated with light so that the magnetic Fe3O4 particles and the polyindole heterojunction photocatalyst promote the reduction of hexavalent chromium.
2. The reduction method according to claim 1, characterized in that: The preparation of magnetic Fe3O4 particles and polyindole heterojunction photocatalyst specifically includes the following steps: Weigh ferric chloride, sodium acetate, and trisodium citrate and dissolve them in ethylene glycol and diethylene glycol solutions to form a mixed solution; The mixed solution is shaken, subjected to a high temperature solvent thermal reaction, and then cooled to room temperature to form a nano-scale magnetic Fe3O4 solution; Weigh indole and dissolve it in the nano-magnetic Fe3O4 solution to form an indole mixed solution; weigh ammonium persulfate and dissolve it in pure water to form an ammonium persulfate solution; The ammonium persulfate solution is added dropwise into the indole mixed solution, and then the solution is shaken and then filtered to obtain nanoscale magnetic Fe3O4 particles loaded with polyindole; the nanoscale magnetic Fe3O4 particles loaded with polyindole are repeatedly washed with pure water to remove impurities, and then vacuum dried and sieved to obtain nanoscale magnetic Fe3O4 particles loaded with polyindole, thereby successfully constructing a magnetic Fe3O4 particle and polyindole heterojunction photocatalyst.
3. The reduction method according to claim 2, characterized in that: The ratio of ethylene glycol to diethylene glycol in the mixed solution is preferably 2:1; the concentration of ferric chloride in the mixed solution is 5-15, preferably 9.9-10.1 g / L; the concentration of sodium acetate in the mixed solution is 30-75, preferably 49.9-50.1 g / L; the concentration of trisodium citrate in the mixed solution is 10-20, preferably 14.9-15.1 g / L.
4. The reduction method according to claim 2, characterized in that: The shaking speed is 400-600 rpm, and the time is 25-35 minutes; preferably, the shaking speed is 500 rpm, and the time is 30 minutes.
5. The reduction method according to claim 2, characterized in that: The temperature of the high-temperature solvent thermal treatment is 190-210° C., and the time is 9-11 hours; preferably, the temperature of the high-temperature solvent thermal treatment is 200° C., and the time is 10 hours.
6. The reduction method according to claim 2, characterized in that: The concentration of indole in the indole mixed solution is 1.6-1.7 g / L.
7. The reduction method according to claim 2, characterized in that: The concentration of the sodium persulfate solution is 1.9-2.1 g / L.
8. The reduction method according to claim 2, characterized in that: The pure water is pure water at room temperature; and / or, the vacuum drying is vacuum drying at 60° C. for 12 hours.
9. The reduction method according to claim 1, characterized in that: The synthesized nano-scale magnetic Fe3O4 particles loaded with polybenzazole are mixed with hexavalent chromium to form a mixed solution; the formed mixed solution is irradiated with light so that the nano-scale magnetic Fe3O4 particles are loaded with polybenzazole to construct a heterojunction to promote the reduction of hexavalent chromium. Specifically, the steps include: Prepare hexavalent chromium aqueous solution; The synthesized nano-scale magnetic Fe3O4 particles loaded with polybenzazole are dispersed in the prepared hexavalent chromium aqueous solution, and the pH value is adjusted to 3.0-4.0, and then stirred evenly to form a mixed solution; a mercury lamp is used as a light source for illumination, and the light is turned on to carry out a reduction reaction.
10. The reduction method according to claim 9, characterized in that: The reduction reaction system is an open system and is not isolated from air; and / or The reduction reaction temperature is controlled at 25±1°C, the reaction time is 0.5-3h, and the light source is a 300W mercury lamp, the wavelength of which is mainly concentrated at 365nm; And / or in the mixed solution, the concentration of the nano-scale magnetic Fe3O4 particles loaded with polybenzazole in the mixed solution is 0.05-0.5 g / L, and the water used in the reaction is ultrapure water.
Citation Information
Patent Citations
Method for treating hexavalent chromium-containing wastewater by photocatalytic reduction of nickel oxide-nickel cobaltate-black titanium dioxide compound
CN110918099A
Method for enriching hexavalent chromium in water body through photochemical reaction
CN113023973A
Polyindole-montmorillonite complex as well as preparation method and application thereof
CN116573711A
Method for degrading new pollutants through rapid cycle light Fenton and application
CN118702913A
Method for treating hexavalent chromium-containing aqueous solution
US20140151302A1